Finding Spiritual Core: Union of the Believers of the Ukrainian Native Faith - SMORZHEVSKA, OKSANA; KHVIST, VICTORIA (Journal of Education, Technology and Computer Science, ISSN 2719-6550, e-ISSN 2719-7417, 2017)
In this article considered Union of the Believers of the Ukrainian Native Faith as Ukrainian ethno-confession, described the institutionalization of this religious organization. Author draws the attention to the ideological basis of confession. Aim of this article - show that modern paganism as the religious-ideological phenomenon has become an important part of the cultural life of Ukraine.